Successful Treatment of Recurrent Adult-Onset Still’s Disease with Tocilizumab: A Case Report and Literature Review - Zhong X; Xu T; Li T; Luo N; Luo N; Hao P (Dove Medical Press, 2023)
Xiaojing Zhong,* Tongtong Xu,* Tianhao Li,* Nana Luo, Nan Luo, Pingsheng Hao Author Affiliations Department of Dermatology, Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, People's Republic of China*These authors contributed equally to this workCorrespondence: Pingsheng Hao, Department of Dermatology, Hospital of Chengdu University of Traditional Chinese Medicine, 39 Shi-Er-Qiao Road, Jinniu District, Chengdu, Sichuan, 610072, People's Republic of China, Tel +86138 8196 5024, Fax +86-28-87732407, Email hpswl@126.comAbstract: Adult-onset Still's disease (AOSD) is considered a rare autoimmune inflammatory disorder with an unclear etiology and pathogenesis.The main clinical manifestations of this disease are high fever, joint pain, and transient skin lesions. Physical examination may reveal hepatomegaly, splenomegaly, and lymphadenopathy, while laboratory tests show abnormalities such as elevated white blood cell count (WBC), erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and serum ferritin (SF). The lack of specific diagnostic markers contributes to a relatively high rate of clinical misdiagnosis and missed diagnoses.In terms of treatment, glucocorticoids have always been the cornerstone medication, but some patients exhibit suboptimal responses to conventional drug therapy, making disease control challenging. However, as our understanding of the pathogenesis continues to grow, novel therapeutic approaches targeting various cytokines have been gradually identified. In this report, we present a case of successful treatment of recurrent AOSD with tocilizumab (TCZ), along with a concise review of innovative treatment strategies for AOSD based on literature retrieval.Keywords: AOSD, tocilizumab, treatment, interleukin-6 inhibitors